Faktor – Faktor yang Mempengaruhi Efektivitas Audit Internal dalam Mewujudkan Good Corporate Governance (Studi Kasus pada Perbankan di Kota Padang Periode 2018 – 2020) - M. Evan Rian Pratama; Dica Lady Silvera (Fakultas Ekonomi, Universitas Ekasakti, 2024)
The influence of implementing auditor competence, the influence of independent auditors and audit committees on internal audit efficiency in fostering good corporate governance (a study of banking in the city of Padang). In this method, primary data is collected through questionnaires, making it a qualitative technique. The participants in this study were internal auditors from eleven different banks in Padang. Internal Audit Effectiveness in Realizing Good Corporate Governance is the dependent variable, and auditor competence, auditor independence, and audit committee independence are the independent variables used in this study. A statistical procedure called multiple regression analysis was used to check the information. Based on the findings, there is no relationship between the use of auditor competence and the effectiveness of internal audit in realizing good corporate governance in banking in the city of Padang. Likewise, there is no correlation between auditor independence and effectiveness, and there is a significant effect of independence on effectiveness. Audit delay, company size, financial health, and profitability are all relevant factors.